Pengaruh Segitiga Kecurangan untuk Mengidentifikasi Kecurangan Laporan Keuangan Menggunakan Variabel Moderasi Penerapan Integrasi Teknologi Industri - Matius John Tirtawirya; Sugeng Riyadi (Penerbit Goodwood, 2021)
Purpose: This study aimed to assess the effectiveness of the fraud triangle in detecting financial statement fraud with the fourth industrial revolution as a phenomenon that is proxied by the application of industrial technology integration as a moderating variable. Research methodology: The fraud triangle consists of pressure, opportunity, and rationalization. Pressure is used to calculate three variables namely financial stability, external pressure, and financial targets. Effective monitoring proxied as an opportunity. And one last variable is rationalization proxied by accruals. Companies included in five priorities sectors on the Making Indonesia 4.0 program have been selected and eliminated, leaving 33 companies as research samples. The logistic regression and subgroup analyses were used in this research. Results: The results indicate that accruals have a positive impact on financial statement fraud, while four additional variables, including financial stability, external pressure, financial targets, and successful monitoring, have no effect on financial statement fraud. Limitations: This study only focused on the five priority sector programs so the results may not be applicable to other sectors. Contribution: Simultaneously, the fraud triangle variables can influence financial statement fraud. Based on the result of subgroup analysis, the application of industrial technology integration is able to moderate the influence of fraud triangle variables on financial statement fraud.